PELATIHAN PRODUKSI PAKAN IKAN MANDIRI SEBAGAI UPAYA EFISIENSI BIAYA DAN KEMANDIRIAN USAHA PEMBUDIDAYA DI DESA PURWASARI - Hamzah, Asep; Benyamin Harris Mofu; Adi Karta Kusuma; Wirasta Driya Wahyu Arifian; Indriana Manik Kaswari; Nurul Farida Efriani; Nurjanna; Abdul Haris Munandar; Febry Aryawan; Nur Afiah Apriliani; Riki Abdilah; Finka Zakiah; Cynthia Cleantha Br. Sinuraya; Aditya Pranata; Maulidal Khairi; Sultansyah Rahman Riyadhi Simbala; Wulan Ali Rahmin; Andi Nurul Wahyuni; Erbid Dwi Pradana; Yasmine Mufidah (Program Studi Budidaya Perairan Universitas Mataram, 2025)
This community service program aimed to enhance the knowledge and technical skills of freshwater fish farmers in Purwasari Village, Dramaga District, Bogor Regency, in producing independent fish feed using locally available ingredients. The program was implemented by the Forum Wacana IPB University team in collaboration with a feed expert from Sultan Ageng Tirtayasa University. The activities consisted of counseling, technical training, and mentoring using a participatory learning approach, allowing participants to be actively involved in every stage of the program. Evaluation through pretest and posttest demonstrated a significant improvement, with an average knowledge increase of 38.1%, particularly in technical understanding and group institutional capacity. Participants showed strong enthusiasm and commitment to continue producing independent feed collectively to reduce production costs and improve business efficiency. The program effectively strengthened farmers’ economic independence and supported the national policy on sustainable fish feed self-sufficiency.